Case of tumor thrombus inside femoral vein, formed by melanoma metastasized to inguinal lymph node. Issue 5 (12th March 2014) - Takai, Toshihiro; Murata, Yozo
Abstract Inguinal lymph nodes are often excised in dermatological surgery, because they are the most common of the lymphatic basin involved in metastasis of malignant skin tumor on the lower extremities or genital region. Herein, we describe a case of cutaneous malignant melanoma on the buttock of a 78‐year‐old woman. Under the huge metastasized inguinal lymph node, there was tumor invasion into the femoral vein with intraluminal tumor thrombus formation. Careful preoperative radiological assessment enabled successful resection on surgery. A review of the published work revealed that tumor thrombus due to direct invasion of melanoma may be rare. The possibility of intravenous tumor thrombus should be considered in the settings of surgery of inguinal metastasis of melanoma, especially when a large‐sized node is located near the great veins.